FOOD SECURITY AND REGIONAL AGRICULTURAL MARKET: ECONOMIC ANALYSIS AND DEVELOPMENT PROSPECTS - Lescheva, Marina; Ivolga, Anna (Economics of Agriculture, 2014)
The analysis of dynamics and current state of an agrifood market is conducted on the case of the agrarian region of Stavropol Krai. The research objective is to analyse development factors and tendencies of the regional agrifood market; to assess the import dependency rate of selected product sectors; to investigate the perspective directions of domestic market saturation. The research subject is a system of economic relations, directed on the establishment and development of the agricultural commodities and food market, and a range of special economic measures for insurance of the food security in the Russian Federation. The analysis includes the market capacity and level of self-sufficiency in the Stavropol Krai, which are defend by basic foodstuffs. It is found that peoples needs in food are covered insufficiently. It is revealed that Stavropol Krai is an active player on both inter-regional and international markets, with the substantial amounts of counter deliveries. Agricultural raw commodities of low added value predominate in export, while processed ones of higher added value – in imports. Food processing industry of the region is underdeveloped, however, it has substantial reserves for development. The major protection measures of domestic food market are defend in the paper: diversification of agricultural production, and industrial and logistics infrastructure development of the regional agrarian market. The results can be used by regional government authorities in improving of the domestic food market regulations.